DAMPAK FINANCIAL DISTRESS DAN KEPEMILIKAN KELUARGA TERHADAP TAX AVOIDANCE DENGAN STRATEGI BISNIS SEBAGAI VARIABEL MODERASI - Khafah Nurfauziah; Adhitya Putri Pratiwi (Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the effect of Financial Distress and family ownership on Tax Avoidance with business strategy as a moderator in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2023. This type of research is quantitative research. The data used in this research are financial statements and annual reports. The sampling technique used in this research was obtained using purposive sampling method, in which from 130 companies from consumer non-cyclical sector, a sample of 27 companies during 5 years was obtained, so that 135 data sample were obtained. The type of data used in this study is secondary data using quantitative research methods. Testing in this study uses the help of the e-views 12. The results of this study indicate that simultaneously financial distress and family ownership have an significant effect on tax avoidance, partially financial distress has no significant effect on tax avoidance, family ownership has a significant and negative effect on tax avoidance, business strategy is unable to moderate financial distress on tax avoidance, business strategy is unable to moderate family ownership on tax avoidance.